Censorship as Cultural Blockage: Banned Literature in the Late Habsburg Monarchy - Wolf, Michaela (TTR, 2002)
AbstractFor Stephen Greenblatt, cultures are “inherently unstable, mediatory modes of fashioning experience,” and it is only through the imaginary order of exclusion that a culture can be simulated as a stable entity. Greenblatt calls such an exclusion “blockage,” a phenomenon that occurs constantly, thereby preventing the collapse of cultural identity. What does this mean for translation practice, where such “blockages,” i.e., textual manipulation or re-writing, can be regarded as constitutive elements of the translation process? This paper examines the question in the particular context of translation practice in the late Habsburg Monarchy. The paper will analyse the different agents which underlie the selection mechanisms–or “exclusion procedures”–in translation and will explore the phenomenon of censorship from both a metaphorical and systemic point of view. The agents involved in the selection of texts to be translated as well as in the selection of translation strategies are manifold and are all interwoven. The selection of texts automatically represents a filter for the analysis of a certain period and is, therefore, a key agent in the reception process. Other important agents are patrons, who are often themselves translators and vital representatives of cultural mediation, as well as translators from various backgrounds, involved to varying degrees in contemporary cultural discourse. Finally, the role of editors, publishers and reviewers as main filters of representations of the cultural Other in a particular culture will be considered. Greenblatt’s model of “cultural blockage” will be examined against this background. Its applicability and limits will be discussed in the context of translation where the issue of the representation of the Other is of paramount importance and where “blockage” definitely illustrates the recognition of cultural distance.